If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12m+24+12=12m+36
We move all terms to the left:
12m+24+12-(12m+36)=0
We add all the numbers together, and all the variables
12m-(12m+36)+36=0
We get rid of parentheses
12m-12m-36+36=0
We add all the numbers together, and all the variables
=0
m=0/1
m=0
| -2(-5+5n)+1=91 | | 5x(x+4)+20=0 | | 4.3/10m=6.21 | | M=5-8.5b | | 4(x-8)=28-8x | | 4(5-5n)+2n=92 | | 1/25x+1/212=2x-3 | | -19+3-11+2y=2 | | -6(14n-11)=-774 | | 18m+36=0 | | x+10=3(x-6) | | 13(x-4)=-169 | | 1x-8+3x+10=90 | | -13(-3-8n)=871 | | 2(-7+3x)=4/ | | 17.6=m+11.3 | | -3=-5(4x+3)+12x= | | 5(2+c)=46 | | x+2-3/4-4/15=0 | | 6(8-14x)=-372 | | -4.8x+1.2=-4.3x+9.2 | | 5-9w=22 | | 7(9+4x)=2(x-3)+2x | | -7(-9x-23)=(-665) | | 3j-7/5=7 | | 11x-3=5x+11 | | 20(10-14a)=412 | | 0.6+v=10.2 | | 4.7x=9.4 | | C-5=-3D+6y | | -9(x+14)=-180 | | I3/5x-5/7I=4/9 |